The print before photography : an introduction to European printmaking, 1550-1820 - Griffiths, Antony, 1951- (London : British Museum press, 2016)
A landmark publication that catalogues the history and development of the printed image Gutenberg's invention of moveable type made it possible to print letters. But images could only be printed using two other technologies that were developed alongside letterpress. One depended on wooden blocks which were cut and printed in relief, the other on copper plates into which lines were cut by engraving or etching and were printed on a rolling press. Copper-plate printmaking developed into a huge business employing thousands of people, and dominated image production for nearly four centuries across the whole of Europe. Its processes remained very stable, and a man of 1500 could have walked into a printing shop of 1800 and understood what was going on. During the nineteenth century this world was displaced by new technologies, of which photography was by far the most important.
Includes bibliographical references (pages 501-545) and indexes.
Keywords: 1500-1799.; 2132 history of the graphic arts; Prints -- Technique -- History; Prints -- Technique; Prints -- Technique; Prints, European -- 16th century; Prints, European -- 17th century; Prints, European -- 18th century; Prints, European; Europa; History